INSIGHTS ON CONSUMER ONLINE PURCHASE DECISIONS OF WOMEN’S FOOTWEAR - SILVA, Susana Costa e; MONTEIRO, Adriana; DUARTE, Paulo (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
Shoes are probably one of the most difficult products to sell online due to the high need-for-touch (NFT) displayed: people need to experiment the product before buying it, more than in any other item. On another hand, women are more prone than men to buy fashion and apparel products through the web channel. This paper investigates the factors driving women consumers to shop footwear products online. A qualitative research method was used grounded on semi-structured, in-depth interviews that were conducted to corroborate the constructs defined in the proposed conceptual model namely: convenience, recreation, NFT and social e-shopping. The interviews were focused on the demand side to understand the female consumers’ perspective and on the top managers of women’s shoes companies representing the suppliers’ viewpoint. The results show that women highly appreciate the convenience that shopping shoes online provides as well as its recreational nature. The NFT also stands out in the shoe market context mainly due to the particularities related to shoe size. Additionally, social e-shopping was found not be as important for women as anticipated as they see social networks more as a communication platform for brands, and less as a factor that influences their predisposition to shop shoes online. On the suppliers’ side, the interviews revealed that managers believe in bloggers and social media influence and its consideration as part of the overall marketing strategy. JEL classification: M30, M31, M160;